The Influence of Pets on the Moral Development of Students - Tomić, Marija J. (Sinteze - časopis za pedagoške nauke , književnost i kulturu, 2024)
Considering the increasing moral hypocrisy of the modern era, it was necessary to focus on the examination of various influences on moral development. Lack of empathy is a phenomenon that is often mentioned when talking about various social deviations. Lack of tolerance, peer violence, various forms of aggressive behavior are sufficient reason to examine morality even at primary school age. This was the main motive for a more detailed investigation level of moral development of elementary school students in Banja Luka. The research was conducted on a sample of 220 eighth and ninth grade students. Based on a short questionnaire and a scale of moral development, the level of development of each student was determined, as well as the gender and type of pet they owned. The final school grades was chosen based on the theoretical analyzes of various psychologists, who specify that age as the end of moral development. In the first part, the paper deals with the theoretical reflection and analysis of previous research, while in the methodological part the hypotheses and the obtained results are analyzed in detail. After the statistical processing of the data, it was determined that there is no statistically significant connection in the level of moral development depending on whether the students have a pet or not. A surprising fact is that more boys than girls have a pet. Although the difference is not statistically significant, it leaves space for the researcher to explore possible causes. An interesting fact is that students who have a rabbit as a pet achieve the highest results on the scale of moral development, followed by students with a dog and a parrot, while those who have a cat or no pet at all achieve the lowest results
Keywords: moral development; pets; gender of students